Balanced into array: genome-wide array analysis in 54 patients with an apparently balanced de novo chromosome rearrangement and a meta-analysis - Feenstra, Ilse (Nature Publishing Group, 2011)
High-resolution genome-wide array analysis enables detailed screening for cryptic and submicroscopic imbalances of microscopically balanced de novo rearrangements in patients with developmental delay and/or congenital abnormalities. In this report, we added the results of genome-wide array analysis in 54 patients to data on 117 patients from seven other studies. A chromosome imbalance was detected in 37% of all patients with two-breakpoint rearrangements. In 49% of these patients, the imbalances were located in one or both breakpoint regions. Imbalances were more frequently (90%) found in complex rearrangements, with the majority (81%) having deletions in the breakpoint regions. The size of our own cohort enabled us to relate the presence of an imbalance to the clinical features of the patients by using a scoring system, the De Vries criteria, that indicates the complexity of the phenotype. The median De Vries score was significantly higher (P=0.002) in those patients with an imbalance (5, range 1–9) than in patients with a normal array result (3, range 0–7). This study provides accurate percentages of cryptic imbalances that can be detected by genome-wide array analysis in simple and complex de novo microscopically balanced chromosome rearrangements and confirms that these imbalances are more likely to occur in patients with a complex phenotype.